Simple method for the estimation of solar spectral radiation - Dahr Fatima-ezzahra; El Alani Omaima; Bah Abdellah; Ghennioui Abdellatif (E3S Web of Conferences, 2021)
In order to know the energy production of photovoltaic modules, it is necessary to have an idea of the spectral distribution of solar radiation, because each technology is characterized by a different spectral resolution. The objective of this work is to determine the irradiance in ultraviolet, visible, and infrared from the triangular shape of the global solar spectrum for any sky state. According to statistical indicators, the coefficient of determination R² varies between 97% and 99%.